2017
DOI: 10.1039/c7cc00461c
|View full text |Cite
|
Sign up to set email alerts
|

Full-colour carbon dots: from energy-efficient synthesis to concentration-dependent photoluminescence properties

Abstract: We present a facile approach, without the need for external heating and any additional energy input, to produce fluorescent carbon dots (CDs) inexpensively and on a large scale. Fluorescence emission wavelengths from the obtained CDs shift gradually from 630 to 400 nm with reduction in their concentration in solution. This work offers a novel avenue for tuning band gaps in CDs and endowing them with potential for various applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
115
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 188 publications
(125 citation statements)
references
References 29 publications
7
115
1
2
Order By: Relevance
“…Wang et al prepared thickness‐dependent emissive CDs ionogel that could emit fluorescence within blue to red color range. Meng et al and Shao et al reported concentration‐dependent CDs with tunable PL from blue to red, respectively. However, despite the numerous reports on the multicolor emissions from CDs, there are still few recent works on precisely controlled up/down‐conversion PL from the same type of CDs under one single excitation wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al prepared thickness‐dependent emissive CDs ionogel that could emit fluorescence within blue to red color range. Meng et al and Shao et al reported concentration‐dependent CDs with tunable PL from blue to red, respectively. However, despite the numerous reports on the multicolor emissions from CDs, there are still few recent works on precisely controlled up/down‐conversion PL from the same type of CDs under one single excitation wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…The decreased distance between each sub-fluorophore induced the electron distribution of SSFPCDs and thus leads to the contraction of previous band gaps as well as Förster resonance energy transfer (FRET) process. [58,59] Since the fluorescence state of SSFPCDs will be contracted into several narrower continuous band gaps with FRET process, an unusual red fluorescence is achieved. To further confirm this mechanism, the temperaturedependent emissions of both the high concentration solution (16.5 mg mL −1 ) and the SSFPCDs powder were tested and analyzed.…”
mentioning
confidence: 99%
“…For excitation-dependent CDs, the fluorescence emission wavelength can be tuned from 400 to 750 nm with a gradual increase in excitation wavelength [34]. The fluorescence intensity of the CDs can also be influenced by environmental factors such as types of solvents [35], Ph [36], temperature [37], and the concentration of CDs [38]. Interestingly, CDs also exhibit up-conversion fluorescence emission that is highly beneficial for in vivo biological applications [24,33,39,40].…”
Section: Carbon Dotsmentioning
confidence: 99%